PATRIARCHY, GENDER EQUALITY AND THE IMPLICATIONS FOR PRODUCTIVE DEVELOPMENT OF THE NIGERIAN WORKER - Okoroafor Ejike C.; E. B. J. Iheriohanma (European Scientific Journal, ESJ, 2014)
The paper focuses on the implications of patriarchy and gender equality on the productive development of Nigerian workforce as it continues to contribute to national development in a fast globalizing 21st century. It aims to determine that patriarchy and gender equality are practically functional tools for the promotion of workers productivity in contemporary Nigeria. It concedes that there is appreciable degree of belief by many Nigerians that patriarchy is a big factor undermining productive advancement of Nigerian workers and also fostering the propagation of social and gender inequalities in the country. Against this belief, the paper submits that the twin concepts of patriarchy and gender equality are potentially working tools for the sustained productivity of Nigerian workers; and therefore recommends, among others, change of perception to support the prevalence of patriarchy and gender equality, effective implementation of gender mainstreaming and meritocracy, eschewing social and political vices within the context of equal respect/treatment for and among all Nigerians.